2001
DOI: 10.1093/ajcn/73.5.853
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional skin care: health effects of micronutrients and fatty acids

Abstract: Human skin is continuously exposed to internal and external influences that may alter its condition and functioning. As a consequence, the skin may undergo alterations leading to photoaging, inflammation, immune dysfunction, imbalanced epidermal homeostasis, or other skin disorders. Modern nutritional science is developing new insights into the relation between food intake and health, and effects of food ingredients may prove to be biologically relevant for optimal skin condition. The objective of this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0
14

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(136 citation statements)
references
References 84 publications
0
122
0
14
Order By: Relevance
“…In fact, topical use of a variety of antioxidants including nutrients such as vitamin C ( 28 ) and vitamin E ( 29 ) has proved effective. Furthermore, there are studies demonstrating that oral intake of those vitamins, carotenoids, and n -3 polyunsaturated fatty acids inhibits actinic skin aging in humans ( 30 ). These data are consistent with those from an epidemiological study ( 31 ) that explored the relationship between actinic skin aging, especially wrinkles, and various foods routinely ingested by the human population all over the world, which varies in terms of races and dietary habits; the epidemiological study showed that aging of the skin was significantly milder in a population taking a large variety of foods including vegetables, olive oil, and fish than in populations with other dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, topical use of a variety of antioxidants including nutrients such as vitamin C ( 28 ) and vitamin E ( 29 ) has proved effective. Furthermore, there are studies demonstrating that oral intake of those vitamins, carotenoids, and n -3 polyunsaturated fatty acids inhibits actinic skin aging in humans ( 30 ). These data are consistent with those from an epidemiological study ( 31 ) that explored the relationship between actinic skin aging, especially wrinkles, and various foods routinely ingested by the human population all over the world, which varies in terms of races and dietary habits; the epidemiological study showed that aging of the skin was significantly milder in a population taking a large variety of foods including vegetables, olive oil, and fish than in populations with other dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that many of the retrieved studies focus on skin as this organ plays a major role in physical appearance, with its functioning and attractiveness known to be dependent on nutrition, particularly the intake of antioxidant vitamins, minerals and essential fatty acids [40].…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…Thus the biological understanding of aging of the skin has made prevention possible and treatments for example tretinoin and alpha-hydroxy acids (Olsen et al, 1992) more efficient. In addition to topical treatments, dietary consumption of certain plants or fish oil have also been found to modulate the balance of lipid inflammatory mediators and are therefore valuable in the treatment of inflammatory skin disorders (Boelsma et al, 2001). A food supplement of marine origin has also been found to improve the appearance of photoaged skin (Heule, 1992;Heule, 1994;Sigler and Rasmussen, 2003;Sigler et al, 2004) after up to 1 year of treatment with no serious side-effects related to the treatment (Kieffer and Efsen, 1998).…”
Section: Introductionmentioning
confidence: 99%